2016
DOI: 10.1007/s13205-016-0547-y
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of p-cresol degradation with polyphenol oxidase (PPO) immobilized in various matrices

Abstract: p-Cresol is an environmental pollutant due to its vast use, toxicity and persistence, nevertheless, its degradation in an enzyme is unclear. In this study, we used Pleurotus sp. isolate VLECK02 polyphenol oxidase (PPO) for the determination of p-cresol degradation. On the basis of UV, FT-IR and chromatographic (HPLC and GC–MS) analysis, 4-methylcatechol was identified as the main metabolite of p-cresol catabolism. In addition, batch and semi-continuous degradation of p-cresol (10 and 20 mM) were studied and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 35 publications
1
8
0
Order By: Relevance
“…Thus, the FT-IR analysis confirmed that p-cresol was degraded into other compounds. This phenomenon has also been reported in the study by Edalli et al, in which the IR spectrum of metabolites produced by the degradation of p-cresol showed shifting of characteristic absorption bands vis-a `-vis at its initiate state (Edalli et al 2016). Furthermore, Huang et al investigated the microbial biodegradation of 3,5xylenol or m-cresol by P. putida NCIMB 9869 through FT-IR spectroscopy (Huang et al 2006).…”
Section: Biodegradation Analysis Of P-cresol Through Ft-irsupporting
confidence: 63%
“…Thus, the FT-IR analysis confirmed that p-cresol was degraded into other compounds. This phenomenon has also been reported in the study by Edalli et al, in which the IR spectrum of metabolites produced by the degradation of p-cresol showed shifting of characteristic absorption bands vis-a `-vis at its initiate state (Edalli et al 2016). Furthermore, Huang et al investigated the microbial biodegradation of 3,5xylenol or m-cresol by P. putida NCIMB 9869 through FT-IR spectroscopy (Huang et al 2006).…”
Section: Biodegradation Analysis Of P-cresol Through Ft-irsupporting
confidence: 63%
“…Other than that, PPOs have been used as biocatalysts in many reactions, with various applications in food, pharmaceutical, and cosmetic industries ( 28 , 29 ) and also as biosensors for the detection of small amounts of phenolics in contaminated waters ( 30 ). Furthermore, they have shown potential in the bioremediation of wastewaters containing phenolic contaminants and for the reduction of chemical oxygen demand ( 28 , 31 , 32 ). As recently reviewed, although laccases have been widely studied, the class of tyrosinases remains underinvestigated, especially concerning its application in the bioremediation of phenolics ( 33 ).…”
Section: Introductionmentioning
confidence: 99%
“…Immobilized enzymes have gained popularity due to several advantages like enzyme recovery, increased stability and durability, rapid enzyme separation from the reaction mixture, tolerance to extreme pH, temperatures and high substrate concentrations [14], [15], [16]. Various techniques like surface binding, gel entrapment (hydrogel), entrapment in reverse micelles, covalent and cross-linking bonding between an enzyme and matrix have been commonly used for improvement in the operational stability of enzymes [17].…”
Section: Introductionmentioning
confidence: 99%